96. Relative Vaccine Effectiveness Against Influenza-Related and Any Respiratory-Related Hospital Encounter During the 2019/20 High Influenza Activity Period: A Comprehensive Real-World Analysis to Compare Quadrivalent Cell-based and Egg-based Influenza Vaccines. (4th December 2021) - Divino, Victoria; Postma, Maarten; Pelton, Stephen I; Mould-Quevedo, Joaquin F; Anupindi, Ruthwik; DeKoven, Mitchell; levin, myron J
Abstract: Background: Changes in the influenza hemagglutinin protein during replication of influenza in eggs during vaccine production may contribute to low vaccine effectiveness (VE). This phenomenon, egg adaptation, can explain VE differences between egg-based (QIVe-SD) and cell-based (QIVc) quadrivalent influenza vaccines. This research evaluated the relative vaccine effectiveness (rVE) of QIVc versus QIVe-SD in the reduction of influenza-related and any respiratory-related hospitalizations/emergency room (ER) visits among subjects 4-64 years old during the 2019/20 influenza season. Methods: A retrospective cohort analysis was conducted among subjects 4-64 years old vaccinated with QIVc or QIVe-SD using administrative claims data in the U.S. (IQVIA PharMetrics ® Plus). The adjusted number of events and rates of influenza-related hospitalizations/ER visits and respiratory-related hospitalizations/ER visits were assessed using inverse probability of treatment weighting (IPTW). Poisson regression was used to estimate relative vaccine effectiveness (rVE). In the main analysis, the study period was from Aug 4, 2019 to Mar 7, 2020 (ending early to avoid any influenza outcome misclassification with COVD-19 infection). In the assessment of the high influenza activity period (HIAP), the analysis period was restricted to Dec 8, 2019 to Mar 7, 2020. Results: During the 2019/20 influenza season, 1, 150, 134 recipients of QIVc and 3, 924, 819, of QIVe-SD were identified following IPTW. In the main analysis, adjusted results show that QIVc was associated with a significantly higher rVE compared to QIVe-SD against influenza-related hospitalizations/ER visits (5.3% [95%CI: 0.5%-9.9%]) and respiratory-related hospitalizations/ER visits (8.2% [95%CI: 6.5%-9.8%]). Similarly, in the HIAP analysis, QIVc was associated with a significantly higher rVE compared to QIVe-SD for influenza-related hospitalizations/ER visits (5.7% [95%CI: 0.8%-10.4%]) and respiratory-related hospitalizations/ER visits (7.3% [95%CI: 5.4%-9.2%]). Conclusion: QIVc was more effective in preventing influenza-related and respiratory-related hospitalizations/ER visits compared to QIVe-SD, using either a broad influenza season definition or restricting to the HIAP. Disclosures: Victoria Divino, PhD, Seqirus (Consultant) Maarten Postma, Dr., Seqirus (Consultant) Stephen I. Pelton, MD, Seqirus (Consultant) Joaquin F. Mould-Quevedo, PhD, Seqirus (Employee) Ruthwik Anupindi, PhD, Seqirus (Consultant) Mitchell DeKoven, PhD, Seqirus (Consultant) myron J. levin, MD, GSK group of companies (Employee, Research Grant or Support)